Difficulties in implementation of systemic solutions of foster care in Poland - Gagacka, Maria (Research Papers of Wrocław University of Economics, 2018)
The aim of the study is to show discrepancies between the intention of the legislator and the actual functioning of solutions contained in the law on family support and foster care adopted in 2011. The article confronts selected system solutions of the Act on Family Support and Foster Care binding from 2012 on secondary institutional sources as well as research results based on literature sources. Analyzing selected legal and organizational solutions, they showed their unsatisfactory social effectiveness. The biggest problem of the current system of foster care is the failure of the available instruments as the result of the lack of a coordination mechanism and, in part, also the will to introduce them. It is all the more incomprehensible that we have not only well diagnosed needs in terms of instruments for family support and foster care, but also recommendations allowing effectively eliminate systemic dysfunctions by implementing adequate coordination mechanisms
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2018, Nr 510, s. 18-31
Keywords: family support; foster care; social policy; family dysfunctions; wsparcie rodziny; piecza zastępcza; polityka społeczna; dysfunkcje rodziny